Parametric study of heat transfer enhancement using impingement of multiple air jets / Niranjan Murthy, V. Krishnan and A. Chennakesava Reddy - Murthy, Niranjan; Krishnan, V.; Reddy, A. Chennakesava (UiTM Press, 2010)
The problem of cooling of electronic components has become a subject of special interest in recent years due to the increasing capacity and rapidly decreasing size of electronic components. Direct contact cooling using multiple jet impingement is considered as the most effective method. The heat transfer problem is complex and better understanding of the jet impingement method is essential for proper application of this method for electronic cooling. Investigations were carried out using electrically heated test plate. Heat flux in the range of 25 to 200 W/cm2, which is a typical requirement for cooling high power electronic components was dissipated using 0.25 mm and 0.5 mm diameter air jets arranged in 7 x 7 array with a pitch of 3 mm. Tests were performed in the Reynolds number range of 1200 to 4500. Results show significant increase in heat transfer co-efficient with increase in heat flux.